Uji Toksisitas Berbagai Formulasi Ekstrak Daun Nilam (Pogostemon cablin) Terhadap Mortalitas Ulat Grayak (Spodoptera sp.): Toxicity of Various Formulation of Nilam Leaf Extract (Pogostemon cablin) on Armyworm Mortality (Spodoptera sp.) - Cecilya Silalahi; Fradilla Swandi (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2026)
Armyworm (Spodoptera sp.) is a polyphagous pest that has a wide range of hosts. This pest can attack when the plants are still young until almost harvest ((Oktober et al., 2024)). Therefore, controlling this pest needs to be done wisely. The continuous use of chemical pesticides will damage the environment and is harmful to the sustainability of the ecosystem. One alternative control that is quite popular is vegetable pesticides. Many vegetable sources have the potential to be developed. Patchouli leaves are one of the potential vegetable sources in controlling armyworm pests. The purpose of this study was to determine the toxicity of patchouli leaf extract in controlling armyworm pests. This study used a non-factorial Completely Randomized Design (CRD) with 10 treatments and 3 replicates. The treatments of this study are K = Control or no treatment, P1 = 1% solid extract, P2 = 2% solid extract, P3 = 3% solid extract, C1 = 1% liquid extract, C2 = 2% liquid extract, C3 = 3% liquid extract, A1 = 1% essential oil, A2 = 2% essential oil and A3 = 3% essential oil. Observations were made in the laboratory. Observations made include mortality observations and GCMS tests of each patchouli leaf extract formulation. The highest mortality parameter was shown by the essential oil formulation. LC50 could only be shown by the essential oil formulation with a concentration value of 0.839 ppm.